2016
DOI: 10.1007/s10660-016-9227-6
|View full text |Cite
|
Sign up to set email alerts
|

Competition in wearable device market: the effect of network externality and product compatibility

Abstract: The rapid growth in consumer adoption of wearable devices has garnered the attention of both practitioners and academia. Competition in the wearable device market is both substantial and complicated. In this study, we investigate the impact of network externality on wearable device competition in a two-dimensional product differentiation model. We consider a market that has a broad array of products (horizontal differentiation) and various quality levels (vertical differentiation). We study two types of networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…This finding might explain why more and more writers are interested in the model of self-publishing. Our finding is consistent with prior literature that the network effect might intensify competition among firms [16], [33]. For example, Foros and Henson reported a similar finding that lower compatibility level can lead to more intense competition between Internet service providers [14].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding might explain why more and more writers are interested in the model of self-publishing. Our finding is consistent with prior literature that the network effect might intensify competition among firms [16], [33]. For example, Foros and Henson reported a similar finding that lower compatibility level can lead to more intense competition between Internet service providers [14].…”
Section: Discussionsupporting
confidence: 92%
“…First, in the standard market, when both self-publishing platforms choose the incompatibility strategy, their revenue will increase when the network effect intensity is greater than a specific threshold and less than the intensity of location preference. Prior studies on competition of software [9] and wearable devices [33] also reported the importance of the network effect intensity. Our results suggest that the conditions of generating more revenue are not difficult for self-publishing platforms to satisfy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wearable devices focus on user communication, providing information in real-time. In certain situations, these devices are superior to handheld devices, such as when tracking vital signs [20,21].…”
Section: Wearable Devices and Agingmentioning
confidence: 99%